Cryopreserving tissue engineered scaffolds within cryobags - Barker , Sven-Alexander; Gryshkov, Oleksandr; Glasmacher, Birgit (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):302